Bridging the Analytical Gap Between Gas Treatment and Reactor Plants in Carbon2Chem®. Issue 10 (2nd August 2022) - Hegen, Oliver; Salazar Gómez, Jorge Iván; Grünwald, Christina; Rettke, Alina; Sojka, Martha; Klucken, Christian; Pickenbrock, Jens; Filipp, Jan; Schlögl, Robert; Ruland, Holger
Abstract: The use of purified process gases as feedstock for subsequent processes requires a detailed verification of the gas purity to ensure long lifetimes of applied catalysts. Herein, the analytical infrastructure for the measurements of the cleaned gases is presented. An overview of all sampling points for the off‐ and on‐line analysis is given. The detailed decryption of the composition of the cleaned blast furnace gas, its main components as well as its traces are presented. Thereby, over 99 % of the overall signal strength of this complex gas matrix measured with a proton transfer reaction mass spectrometer with H3 O + as reagent ion could be revealed. Furthermore, by the example of the catalyst poison H2 S, the necessity of monitoring continuously the gas matrix for certain compounds was proven. Abstract : Analytics in the bigger picture. In this article the reasons why detailed gas analytics are essential for the success of Carbon2Chem® are presented and a deeper insight in the installed analytical infrastructure as well as its application is provided.